Analisis Kinerja Kepemimpinan dan Produktivitas Kerja Karyawan Pada Bank Syariah Indonesia Cabang Stabat - Hapsyah, Hapsyah; Harahap, Muhammad Arfan; Badar, As’ad (Universitas Muhammadiyah Sumatera Utara, 2023)
Based on this background, the authors formulate the objectives of this study, namely: To determine the performance of leadership in the Stabat Branch of Bank Syariah Indonesia. To find out the performance of leadership and work productivity of Bank Syariah Indonesia Stabat Branch employees. To find out the obstacles in maximizing leadership and employee work productivity at the Stabat Branch of Bank Syariah Indonesia. The method used in this study is qualitative research using data collection techniques through observation, interviews and documentation. After carrying out a series of stages of the research above, it can be concluded that leadership performance in increasing employee work productivity at the Stabat Branch of Islamic Bank Indonesia, namely carried out by employee development and compensation in an Islamic economic perspective, both are overall very good. This can be seen from the development program that is applied to provide increased understanding of employees so that they have kafa'ah properties or have expertise in work, are trustworthy or can be trusted in carrying out their duties and himaatulah charity or have good work behavior and compensation that is based on agreement and willingness, have met basic needs and are given in a transparent manner in accordance with their respective positions which are said to be quite fair and proper, thereby encouraging employee enthusiasm to further increase their work productivity at Bank Syariah Indonesia KCP Stabat